Language standardization and language change : the dynamics of Cape Dutch - Deumert, Ana (Impact, studies in language and society, 2004)
Language Standardization and Language Change describes the formation of an early standard norm at the Cape around 1900. The processes of variant reduction and sociolinguistic focusing which accompanied the early standardization history of Afrikaans (or 'Cape Dutch' as it was then called) are analysed within the broad methodological framework of corpus linguistics and variation analysis. Multivariate statistical techniques (cluster analysis, multidimensional scaling and PCA) are used to model the emergence of linguistic uniformity in the Cape Dutch speech community. The book also examines langu.